Soko Property as A Dzurri Waqf in The Preservation Of Family Heritage According To The Perspective of Maqashid Shari'ah : (A Study Of Customary Analysis in Kampar Regency) - IchsanAnwari, Ferry; Kasmidin, Kasmidin; Maghfirah, Maghfirah (Fakultas Hukum dan Ekonomi Syariah Institut Agama Islam Pangeran Dharma Kusuma Indramayu, 2025)
This study raises the problem of property distribution with the pattern of distribution of soko property which aims to preserve family inheritance as an equation with the concept of dzurri waqf in the Kampar community according to the analysis of maqashid shari'ah. This study aims to answer doubts about the chronology of the emergence of soko assets in the tradition of inheriting property in the Kampar community, the practice of implementing the distribution of soko assets which is equated with the concept of dzurri waqf, and a review of maqashid shari'ah on this distribution pattern. The method used is a qualitative research method where the method in this study is the main source of data obtained by conducting direct research on the tradition of the distribution of soko property by observing the situation in the field and then describing and analyzing so that it can answer the problems that have been formulated in the problem formulation. This study uses data collection methods with observation, interviews, and documentation studies. After the data is obtained based on the subject matter, a qualitative data analysis method with a descriptive approach is used. The results of this study show that the soko property in the Kampar people's customs emerged based on the culture brought by the Kampar limo koto custom which originated from the Minangkabau country, where the majority of family relationships are based on matrilineal. The positive impact of the distribution of soko property is to maintain the preservation of family property and protect the descendants of women. Meanwhile, the negative impact is that there are several families who deliberately sell the property to outsiders by violating customary advice, and are not serious in managing the property so that it is far from productive value. Then the solution if there is a conflict of division and management, gradual mediation such as mediation between families, mediation between ninik mamak, and the last step through the positive legal process in Indonesia. The review of maqashid shari'ah on soko property is to meet the needs of dharuriyyat, hajjiyyat, and tahsiniyyat.